Explorando el potencial del litio peruano: retos y oportunidades - Rivera Daza, Pamela (Pontificia Universidad Católica del Perú, 2023)
The article explores the potential of lithium in Peru, addressing the challenges and opportunities to achieve sustainable development and generate economic and social impact. Peru has significant lithium reserves, but the lack of clear and effective regulation has limited foreign investment. The importance of addressing social and environmental issues is highlighted. In addition, the relevance of lithium in the manufacture of rechargeable batteries for electric vehicles and renewable energy storage systems is discussed. Finally, the article concludes that the potential of lithium to contribute to the transition towards a low carbon economy is considerable but requires a coherent and transparent strategy to guarantee its sustainable exploitation.

El artículo explora el potencial del litio en Perú, abordando los desafíos y oportunidades para lograr un desarrollo sostenible y generar impacto económico y social. Perú cuenta con reservas significativas de litio, pero la falta de regulación clara y efectiva ha limitado la inversión extranjera. Se destaca la importancia de abordar los problemas sociales y ambientales. Además, se discute la relevancia del litio en la fabricación de baterías recargables para vehículos eléctricos y sistemas de almacenamiento de energía renovable. Por último, el artículo concluye que el potencial del litio para contribuir a la transición hacia una economía baja en carbono es considerable, pero requiere una estrategia coherente y transparente para garantizar su explotación sostenible.
Exploring the potential of Peruvian lithium: challenges and opportunities
Keywords: Lithium; Peru; Challenges; Opportunities; Sustainable development; Economic impact; Social Impact; Regulation; Litio; Perú; Desafíos; Oportunidades; Desarrollo sostenible; Impacto económico; Impacto Social; Regulación; https://purl.org/pe-repo/ocde/ford#5.05.00